Ijtihad of the Companions in Determining Grandfather's Inheritance Rights with Brothers and Sisters - Zuhdi, M; Miharja, Marjan; Rahmawati, Dyah (Nurani, 2023)
The rule on the part inherited by the grandfather together with the siblings of the testator is not found at all from the nagli arguments in the Qur'an or as-Sunnah. The provisions of their share are found through the ijtihad of the Companions. The ijtihad of the Companions has differences with each other. Thus, it is important to conduct an in-depth study of the ijtihad of the Companions. The issue to be discussed in this research is how the grandfather's share of inheritance rights if he is with brothers and sisters based on the ijtihad of the Companions. The purpose of the research is to conduct a study of the grandfather's share of inheritance if he is with brothers and sisters according to the ijtihad of the Companions. This research uses a type of qualitative research whose data comes from secondary data. Documentation study was chosen in collecting data, while data analysis was carried out in three stages, namely data reduction, data verification and data presentation. The results of this study reveal that there are still things that require ijtihad in resolving the issue of grandfather's share of inheritance with the inheritor's siblings that occur in the community. The findings are based on the example of calculating inheritance according to the opinions of Abu Bakr, Zaid bin Tsabit, Umar and Ibn Mas'ud.